Sintesis keton dari asam lemak stearat dengan katalis layered double hydroxide (LDH) Mg-Al-Cu - Firman Arief Soejana; Erliza Hambali; Obie Farobie (AGROINTEK, 2024)
The synthesis of ketones from stearic fatty acids using the fatty acid decarboxylation method to ketones has been carried out to increase the added value of palm oil derivative products. One of the derivative products of palm oil is Crude Palm Oil which can be converted into fatty acids through the triglyceride hydrolysis process. Palm fatty acids are Indonesia's most potentially environmentally friendly raw material. This research aims to synthesize ketones from palm fatty acids using a catalyst. Ketone compounds were synthesized using a solid base catalyst as a double hydroxide layer based on Mg-Al-Cu. Identification of the presence of a C=O ketone group was carried out by testing the Fehling test, Tollens, spectrophotometer (FTIR), and computing the yield. The results showed the success of ketone synthesis using the fatty acid decarboxylation method into ketones through a test of Fehling's on stearic fatty acid ketone products. Meanwhile, in the Tollens test, there wasn't a change in the silver mirror. Furthermore, the spectrophotometer test (FTIR) showed the presence of a C=O bond or a carbonyl group at the peak wave 1707 cm-1. Ketone's synthesis produced was 95.09%.